La Economía del Hidrógeno como Solución al Problema de la Estabilización del Clima Mundial - Berry, Gene D.; Aceves, Salvador M. (Acta Universitaria, 2006)
Unlike other fuels, hydrogen (H2) can be generated and consumed without generating carbon dioxide (CO2). This creates both significant engineering challenges and unsurpassed ecological advantages for H2 as a fuel, while enabling an inexhaustible (closed) global fuel cycle based on the cleanest, most abundant, natural, and elementary substances: H2, O2, and H2O. If generated using light, heat, and/or electrical energy from solar, wind, fission, or (future) fusion power sources, H2 becomes a versatile, storable, and universal carbonless energy carrier, a necessary element for future global energy system(s) aimed at being free of air and water pollution, CO2, and other greenhouse gases. The case for hydrogen rests fundamentally on the need to eliminate pollution and stabilize Earth’s atmosphere and climate system.
Keywords: Array; Array; Array